Relation of Neck Circumference with Total Body Fat and BMI - Papandreou, Dimitrios; Causapin, Mark; Tul-Noor, Zujaja; Malindretos, Pavlos (Current Nutrition & Food Science, 2016)
Purpose: The prevalence of obesity in United Arab Emirates (UAE) has reached alarming rates during the last decade. Neck Circumference (NC) is a simple measure that can identify obesity levels. However, no studies in UAE so far have studied the connection of NC with other anthropometric measurements. The aim of this study was to determine the relationship between NC and obesity. Methods: Two hundred and forty-three female students participated in the study. Anthropometric data was also collected from all subjects. The study was approved by the ethical committee of the university and a consent form was signed by all participating subjects. Results: Based on under the area curve (AUC), obesity was defined with NC >31.25cm. Pearson correlation analysis showed a significantly moderate relationship between obesity and BMI (r=0.454, P<0.001), obesity and Body Fat (BF) (r=0.429, P<0.001) and obesity and waist circumference (WC) (r=0.365, P<0.001). In multiple regression analysis, BMI (Beta: 2.348, 95% CI:1.01, 3.512, P<0.011) and TBF% (1.291, 95% CI:1.04,1.381, P<0.030) were found independently associated with NC for obesity. Conclusion: NC is a potential tool for measuring obesity. A value of NC >31 cm may be used as a cut off level for determining obesity in female college students. TBF and BMI were also independently associated with NC.
Keywords: female students